Hyperactivity of medial prefrontal cortex pyramidal neurons occurs in a mouse model of early-stage Alzheimer’s disease without β-amyloid accumulation - Choudhury, Nasreen; Chen, Lihua; Al-Harthi, Lena; Hu, Xiu-Ti (Frontiers in Pharmacology, 2023)
The normal function of the medial prefrontal cortex (mPFC) is essential for regulating neurocognition, but it is disrupted in the early stages of Alzheimer’s disease (AD) before the accumulation of Aβ and the appearance of symptoms. Despite this, little is known about how the functional activity of mPFC pyramidal neurons changes as AD progress during aging. We used electrophysiological techniques (patch-clamping) to assess the functional activity of mPFC pyramidal neurons in the brain of 3xTg-AD mice modeling early-stage AD without Aβ accumulation. Our results indicate that firing rate and the frequency of spontaneous excitatory postsynaptic currents (sEPSCs) were significantly increased in mPFC neurons from young AD mice (4-5-months, equivalent of <30-yr-old humans) compared to age-matched control mice. Blocking ionotropic glutamatergic NMDA receptors, which regulate neuronal excitability and Ca2+ homeostasis, abolished this neuronal hyperactivity. There were no changes in Ca2+ influx through the voltage-gated Ca2+ channels (VGCCs) or inhibitory postsynaptic activity in mPFC neurons from young AD mice compared to controls. Additionally, acute exposure to Aβ42 potentiated mPFC neuronal hyperactivity in young AD mice but had no effects on controls. These findings indicate that the hyperactivity of mPFC pyramidal neurons at early-stage AD is induced by an abnormal increase in presynaptic glutamate release and postsynaptic NMDA receptor activity, which initiates neuronal Ca2+ dyshomeostasis. Additionally, because accumulated Aβ forms unconventional but functional Ca2+ channels in mPFC neurons in the late stage of AD, our study also suggests an exacerbated Ca2+ dyshomeostasis in mPFC pyramidal neurons following overactivation of such VGCCs.